Interrogatory Theology - Hoffmeyer, John F. (Dialog, 2008)
Theological engagement with young people—and indeed with people of all ages—benefits when it attends to the practice of asking questions. The understanding of theological statements requires an appreciation of the questions behind them. In addition, questions are not merely instruments for getting to the answers. Good questions themselves generate insight. Questioning works best in an atmosphere of trust and freedom. This article develops these points by narrating experiences of theological engagement with young people.